An investigation into management of assets: the case of Ministry of Media, Information and Publicity - Samakonde, Erinera (Midlands Sate University, 2015)
Asset management is an area that is increasingly neglected by most central governments, the research investigates into the management of assets. The research was aimed at investigating the causes of poor asset management and to find ways of improving the management of assets. The quantitative descriptive case study was used as a methodology of research .The Ministry of Media, Information and Publicity was the targeted participant in this study. The collection of primary data was done through thirty-five questionnaires and five interviews. The population of the study included the Deputy Directors, Accountants, Administration Officers, and Auditors in the ministry. The sample was made up of forty participants conveniently selected and judgemental sampling method was used. The results of the study indicated that there is poor asset management due to the absence of Asset management framework, updated Asset Register, effective information system for Asset management and lack of competent skills. It is recommended that best practise of asset management framework, policies and procedural document be developed. A further study is proposed to research the methodology on the capitalisation of assets and to determine the effectiveness of using Cash and accrual accounting for Asset Management.